2019
DOI: 10.3389/fnins.2019.00496
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Acupuncture Ameliorated MPTP-Induced Parkinsonism in Mice via TrkB Neurotrophic Signaling

Abstract: Neurotrophins, such as brain-derived neurotrophic factor (BDNF), have shown promise as neuroprotective agents, indicating their potential in therapeutic strategies for neurodegenerative disease. However, the inherent bioactivity and pharmaceutical limitations of BDNF compromise its clinical efficacy. Research has documented the beneficial effects of electroacupuncture (EA) against neurodegeneration, possibly by BDNF-mediated mechanisms. The present study was designed to clarify whether EA can mount a neuroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Evidences revealed that acupuncture or EA could ameliorate motor symptoms and reduce dopaminergic neuronal degeneration in PD models [35][36][37][38]. In our present experiment, chronic EA treatment ameliorated gross motor signs (ambulatory activity and coordinated balance ability) and ne forelimb motor performance in a partial-lesioned model.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Evidences revealed that acupuncture or EA could ameliorate motor symptoms and reduce dopaminergic neuronal degeneration in PD models [35][36][37][38]. In our present experiment, chronic EA treatment ameliorated gross motor signs (ambulatory activity and coordinated balance ability) and ne forelimb motor performance in a partial-lesioned model.…”
Section: Discussionsupporting
confidence: 64%
“…2a, c). Contrasting with application of EA immediately after toxic administration [35] [36] [37], we delivered EA two weeks after 6-OHDA lesion. Thus, it is speculated that chronic 6-OHDA lesion induced irreversible neuronal death in the SNc which could not be reversed by subsequent EA treatment [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were evaluated for motor impairments with a rotarod apparatus (Harvard apparatus, Holliston, MA, USA) as described [ 26 , 27 ]. In brief, at 3 days after last dosage of MPTP treatment, mice were subjected to behavioral assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TrkB cleavage by calpain impairs the BDNF function [73]. Furthermore, MPTP increased the level of TrkB.T1 expression [74]. Additionally, Rbfox1 (RNA-binding protein fox-1 homolog), a neuron-specific splicing factor, was one among the most consistently upregulated genes identified in the transcriptome of midbrain dopaminergic (mDA) neurons of PD patients [75].…”
Section: The Function Of Trkb Isoform In Pdmentioning
confidence: 99%